Pemanfaatan Jerami Kacang Tanah dan Kacang Hijau sebagai Bahan Green Concentrate di Kabupaten Serang - Jayanti Malik, Rika; Mutmainnah, Hijriyah; Muttakin, Syahrizal; Widiyastuti, Dewi; Hidayah, Ismatul (Balai Pelatihan Pertanian Jambi, 2023)
The objective of the study was to analyze the ability of the Karya Tani group to utilize peanut and mung bean straw as green concentrate ingredients. The study was conducted at Mekarsari Village, Anyar District, Serang Regency. The qualitative study method used pilot techniques for peanut and mung bean cultivation. The findings revealed that (1) Peanuts planted with a spacing of 40x20 cm had the highest performance, but peanut plants planted with a spacing of 40x40 cm produced the majority of leaves, and the average height of peanut plants aged 50-55 days after planting was 58.3 cm with 360 leaves/plant; (2) The average size of mung bean plants 70 days after planting was 49 cm with 25 leaves/plant; (3) Peanut productivity of 1.9 tons/ha produces a stover of 0.7 tons/ha. Green bean productivity is 1 ton/ha with a stover weight of 1 ton/ha; (4) the Karya Tani group can utilize peanut and mung bean waste as green concentrate material. The nature of the utilization of peanut stover is complementary to Indigovera plants. With a total of 2.6 tons of stover, it can meet the needs of 139 sheep for two months. The Karya Tani Group should be sustainable in cultivating legume-sourced food crops and indigo vera development to maintain the availability of quality sheep feed.